Experimental epileptogenesis in a cell culture model of primary neurons from rat brain: A temporal multi‐scale study - Jablonski, Janos; Hoffmann, Lucas; Blümcke, Ingmar; Fejtová, Anna; Uebe, Steffen; Ekici, Arif Bülent; Gnatkovsky, Vadym; Kobow, Katja (Cells, 2021)
Understanding seizure development requires an integrated knowledge of different scales of organization of epileptic networks. We developed a model of “epilepsy‐in‐a‐dish” based on dissociated primary neuronal cells from neonatal rat hippocampus. We demonstrate how a single application of glutamate stimulated neurons to generate spontaneous synchronous spiking activity with further progression into spontaneous seizure‐like events after a distinct latency period. By computational analysis, we compared the observed neuronal activity in vitro with intracranial electroencephalography (EEG) data recorded from epilepsy patients and identified strong similarities, including a related sequence of events with defined onset, progression, and termination. Next, a link between the neurophysiological changes with network composition and cellular structure down to molecular changes was established. Temporal development of epileptiform network activity correlated with increased neurite outgrowth and altered branching, increased ratio of glutamatergic over GABAergic synapses, and loss of calbindin‐positive interneurons, as well as genome‐wide alterations in DNA methylation. Differentially methylated genes were engaged in various cellular activities related to cellular structure, intracellular signaling, and regulation of gene expression. Our data provide evidence that a single short‐term excess of glutamate is sufficient to induce a cascade of events covering different scales from molecule‐ to network‐level, all of which jointly contribute to seizure development.
CRIS-Team Scopus Importer:2021-11-12
Keywords: DNA methylation; Epigenetic; Epilepsy; In vitro